2018
DOI: 10.1071/hc17089
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a stratified random sample of New Zealand general practices

Abstract: INTRODUCTION Practice size and location may affect the quality and safety of health care. Little is known about contemporary New Zealand general practice characteristics in terms of staffing, ownership and services. AIM To describe and compare the characteristics of small, medium and large general practices in rural and urban New Zealand. METHODS Seventy-two general practices were randomly selected from the 2014 Primary Health Organisation database and invited to participate in a records review study. Forty-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 25 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…Analysis of the characteristics of the general practices of the original SHARP study showed that large practices had significantly higher numbers of patients enrolled per full-time-equivalent (FTE) general practitioner (GP) (mean 1827 patients per FTE GP) compared with medium-sized practices (mean 1457 patients/FTE GP) and small practices (mean 1120 patients/FTE GP) but similar practice nurse workloads. 24 International literature on the linkage between practice size, patient caseload for the general practice team and quality and continuity of primary care is mixed. An English study of over 230 000 patients showed that better continuity of care with one’s own GP was associated with reduced rates of preventable hospital admissions and that larger practices (>7 FTE GPs) had lower levels of continuity than smaller practices (1–3 FTE GPs).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the characteristics of the general practices of the original SHARP study showed that large practices had significantly higher numbers of patients enrolled per full-time-equivalent (FTE) general practitioner (GP) (mean 1827 patients per FTE GP) compared with medium-sized practices (mean 1457 patients/FTE GP) and small practices (mean 1120 patients/FTE GP) but similar practice nurse workloads. 24 International literature on the linkage between practice size, patient caseload for the general practice team and quality and continuity of primary care is mixed. An English study of over 230 000 patients showed that better continuity of care with one’s own GP was associated with reduced rates of preventable hospital admissions and that larger practices (>7 FTE GPs) had lower levels of continuity than smaller practices (1–3 FTE GPs).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve practices were randomly selected by from each strata and invited to participate; 44 study practices consented to participate (72.6% of the 62 eligible randomly selected practices with compatible practice software). 11…”
Section: Methods Settingmentioning
confidence: 99%
“…9 In this study we examine medication-related harm in general practice using a subset of data from a nation-wide retrospective cohort review of general practice electronic health records which was looking at all harms. 10,11 The primary aim of this paper was to estimate the incidence, preventability and severity of all harms attributable to medication prescribed in general practice in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…18 We randomly selected 72 practices nationally and invited the 62 eligible practices to participate. 19 Forty-five practices agreed (73%). The most common reasons for non-participation were commitment to confidentiality, concern about secondary use of data for financial gain, and fear of accountability repercussions.…”
Section: Confidentiality: the Ethical Dutymentioning
confidence: 99%